Preparation method of cobalt-doped bismuth ferrite film system material

BiFe1-xCoxO3 film was prepared by solvent gel method and pulsed laser deposition method, which solved the problem of lattice defects in BiFeO3 film affecting its properties, achieved the growth and magnetic regulation of high-quality films, and enhanced the magnetic properties of the film.

CN119876849AInactive Publication Date: 2025-04-25KUNMING UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510087630.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Lattice defects in BiFeO3 films affect their physical properties, and it is difficult for the prior art to effectively adjust their ferroelectricity and magnetic properties.

Method used

Cobalt-doped bismuth ferrate film was prepared by solvent gel method, and BiFe1-xCoxO3 film was grown on LaAlO3 substrate by pulsed laser deposition method, and the cobalt doping ratio was adjusted to control the ferroelectricity and magnetic properties of the film.

Benefits of technology

It achieves high-quality film growth with high phase purity, can adjust the magnetic strength, enhance the magnetic properties of the film, and has good electrohysteresis loops and butterfly curves.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876849A_ABST
    Figure CN119876849A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a cobalt-doped bismuth ferrite film system material, the film material is BiFe1-xCoxO3 (wherein x is 0.02-0.10), a sol-gel method is used for preparing initial powder, and then the initial powder is tabletted and sintered into a ceramic target material. And sputtering and depositing the ceramic target material on a LaAlO3 substrate by using a pulse laser deposition technology to prepare the BiFe < 1-x > CoxO3 system thin film. According to the invention, the solvent gel method is adopted to ensure the mixing of the components at the molecular level, the ceramic target material is high in density, the epitaxial growth film is high in phase-forming purity and shows excellent ferroelectricity and magnetism, the method is simple in process, the selected chemical reagents are low in price and easy to obtain, and the method is suitable for industrial production. According to the BiFe < 1-x > CoxO < 3 > system film sample, an atomic level flat morphology graph and a good ferroelectric domain overturning characteristic are observed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic functional thin film materials, and in particular relates to a method for preparing a cobalt-doped bismuth ferrite thin film system material. Background Art

[0002] In recent years, with the rapid development of ferroelectric memory, photocatalytic degradation, high-temperature piezoelectric devices, energy storage dielectrics and ferroelectric photovoltaics, thin film materials with excellent ferroelectric and piezoelectric properties have become one of the hot topics in the current research field.

[0003] Multiferroic magnetoelectric materials refer to a class of materials that have both ferroelectric (antiferroelectric) and ferromagnetic (antiferromagnetic) properties. This type of material has broad application prospects in ferroelectric memory, photocatalytic degradation, high-temperature piezoelectric devices, energy storage dielectrics, and ferroelectric photovoltaics. Bismuth ferrite (BiFeO3) has become a class of lead-free and environmentally friendly materials comparable to lead-based materials due to its room-temperature multiferroic properties (ferroelectric Curie temperature is 1103K and antiferromagnetic Neel temperature is 643K), providing great application possibilities for the development of new information storage and processing based on ferroelectric-magnetic integrated effects and magnetoelectric devices. However, lattice defects (such as ionic oxygen vacancies) in BiFeO3 films have attracted widespread attention because their presence can affect physical properties such as electron transport, magnetism, and ferroelectricity. Here, we use electric field to regulate the BiFe 1-x Co x The conductive state of the O3 film, the addition of divalent cobalt ions can improve the corresponding magnetic properties. The ferroelectricity and magnetism of the film can be adjusted by controlling the doping ratio. Summary of the invention

[0004] In view of the above problems, the present invention provides a cobalt-doped bismuth ferrite film capable of adjusting ferroelectricity and magnetism and a preparation method thereof.

[0005] The method for preparing the cobalt-doped bismuth ferrite thin film system material of the present invention specifically comprises the following steps:

[0006] (1) Chemicals cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, and ferric nitrate nonahydrate were mixed into a solution of BiFe 1-x Co x The chemical molar ratio of the O3 element is calculated and weighed, and then the citric acid is weighed, and the weighed mixture is added to a beaker, and then the solvents methanol and ethylene glycol are added in sequence, and then the beaker is placed on a table with a constant temperature and uniform magnetic force and stirred evenly, and after a period of time, a fully mixed and uniform solution is obtained;

[0007] (2) stirring and heating the uniform solution of step (1) for a period of time, until the mixed solvent of methanol and ethylene glycol evaporates and generates a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a corresponding substance gel, scraping the gel from the beaker, putting it into a mortar and grinding it thoroughly to obtain a cobalt-doped bismuth ferrite ceramic powder, placing the cobalt-doped bismuth ferrite ceramic powder into a box furnace for pre-sintering treatment, controlling the heating rate, initial sintering time, and sintering temperature to obtain a primary calcined powder;

[0008] (3) placing the primary calcined powder in step (2) into a specially customized mold and subjecting it to pressure treatment to prepare a cobalt-doped bismuth ferrite ceramic block, and placing the obtained ceramic block into a muffle furnace for calcination to obtain a cobalt-doped bismuth ferrite ceramic target;

[0009] (4) The bulk target was deposited on a LaAlO3 substrate using pulsed laser deposition to obtain BiFe 1-x Co x O3 film.

[0010] In the step (1) of the present invention, x=0.02-0.10, the molar ratio of citric acid to the metal cation of cobalt-doped bismuth ferrite is 1:1, the volume ratio of methanol to ethylene glycol is 4:1, the stirring time is 40 minutes, and the magnetic speed is 300 r / min.

[0011] In step (2) of the present invention, the heating temperature of the mixed solution is 80-100°C, the heating time is 1h, the oven drying temperature is 140°C, the drying time is 18h, the grinding time is 0.5h, the heating rate is 4°C / min, the initial sintering temperature is 500°C, the initial sintering time is 4h, and the sintering conditions are normal pressure and air atmosphere.

[0012] In step (3) of the present invention, the pressure of the tablet press is 1-2Mpa, the pressurization time is 20min, the calcination temperature is 900°C, the heating time is 2h, and the sintering conditions are normal pressure and air atmosphere.

[0013] In step (4) of the present invention, BiFe 1-x Co x O3 target is used for pulsed laser deposition to grow thin films. When the vacuum degree of the chamber reaches 1×10 -4 When the energy of the pulse laser is adjusted to 250mJ, pre-sputtering is performed. After sputtering, the heating temperature is set to 700℃, the oxygen pressure in the chamber is adjusted to 20Pa, and a bottom electrode is grown first; after the bottom electrode is grown, BiFe 1- x Co x O3 film, set the temperature to 650℃, adjust the oxygen pressure to 13.3Pa; after the growth is completed, introduce 2×10 4Pa oxygen annealing, cooling rate 10℃ / min, annealing time 45min, BiFe 1-x Co x O3 film.

[0014] Beneficial effects of the present invention:

[0015] The purpose of the present invention is to provide a method for preparing a cobalt-doped bismuth ferrite thin film system material. The present invention adopts a solvent gel method to ensure the mixing of various components at the molecular level, and the epitaxially grown film has good quality, good crystallinity, and high phase purity. The method is simple in process, good in repeatability, and the selected chemical reagents are inexpensive and easy to obtain, with a high yield rate, and BiFe 1-x Co x Atomic-level flat morphology, good hysteresis loop and butterfly curve were observed for the O3 system thin film samples. The magnetism was enhanced by controlling the strength of magnetism by adjusting the cobalt doping ratio. However, due to the limitation of nano-level magnetic testing technology, the relevant magnetism cannot be effectively measured. However, it is expected to be applied in information storage, mobile communications, electronics, aviation and other industries in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Example 1BiFe 1-x Co x XRD pattern of O3 thin film system materials;

[0017] Figure 2 Example 1BiFe 0.98 Co 0.02 AFM morphology of O3 thin film system materials;

[0018] Figure 3 Example 1BiFe 0.98 Co 0.02 Hysteresis loop and butterfly curve of O3 thin film system materials;

[0019] Figure 4 Example 1BiFe 0.95 Co 0.05 AFM morphology of O3 thin film system materials;

[0020] Figure 5 Example 1BiFe 0.95 Co 0.05 Hysteresis loop and butterfly curve of O3 thin film system materials;

[0021] Figure 6 Example 1BiFe 0.90 Co 0.10 AFM morphology of O3 thin film system materials;

[0022] Figure 7 Example 1BiFe 0.90 Co 0.10 Hysteresis loop and butterfly curve of O3 thin film system materials; DETAILED DESCRIPTION

[0023] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited to the described contents.

[0024] Example 1

[0025] (1) Chemicals cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, and ferric nitrate nonahydrate were mixed into a solution of BiFe 1-x Co x The chemical molar ratio of the O3 element is calculated and weighed, x = 0.05, and then citric acid is weighed, and the weighed mixture is added to a beaker, and then the solvents methanol and ethylene glycol are added in sequence, and the volume ratio of methanol to ethylene glycol is 4:1. A magnetic stirrer is placed in the beaker, and the beaker is placed on a table with a constant temperature and uniform magnetic force for uniform stirring. The magnetic speed is controlled, and a uniform solution is obtained after a period of time. The stirring time is 40 minutes, and the magnetic speed is 300r / min;

[0026] (2) moving the uniform solution of step (1) to a heated magnetic uniform table for stirring and heating for a period of time, the heating temperature is 80°C, the heating time is 1 hour, and the mixed solvent of methanol and ethylene glycol evaporates and generates a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a gel, the oven drying temperature is 140°C, the drying time is 18 hours, scraping the gel from the beaker, putting it into a pre-cleaned mortar and grinding it thoroughly, the grinding time is 0.5 hours, and cobalt-doped bismuth ferrite ceramic powder is obtained, and the cobalt-doped bismuth ferrite ceramic powder is placed in a box furnace for pre-sintering treatment, the heating rate is 4°C / min, the initial sintering temperature is 500°C, the initial sintering time is 4 hours, and the sintering conditions are normal pressure and air atmosphere to obtain a primary calcined powder;

[0027] (3) placing the primary calcined powder in step (2) into a circular mold and subjecting it to pressurization treatment, the pressure of the tablet press is 1 to 2 MPa, the pressurization time is 20 min, and a cobalt-doped bismuth ferrite ceramic block is prepared. The obtained ceramic block is placed in a box-type furnace for calcination, the calcination temperature is 900° C., the heating time is 2 h, and the sintering conditions are normal pressure and air atmosphere, thereby obtaining a cobalt-doped bismuth ferrite ceramic target;

[0028] (4) BiFe 0.95 Co 0.05 O3 target is used for pulsed laser deposition to grow thin films. When the vacuum degree of the chamber reaches 1×10 - 4When the energy of the pulse laser is adjusted to 250mJ, pre-sputtering is performed. After sputtering, the heating temperature is set to 700℃, the oxygen pressure in the chamber is adjusted to 20Pa, and a bottom electrode is grown first; after the bottom electrode is grown, BiFe 1-x Co x O3 film, set the temperature to 650℃, adjust the oxygen pressure to 13.3Pa; after the growth is completed, introduce 2×10 4 Pa oxygen annealing, cooling rate 10℃ / min, annealing time 45min, BiFe 0.95 Co 0.05 O3 film.

[0029] The BiFe prepared in this example 0.95 Co 0.05 The XRD pattern of O3 film is as follows Figure 1 As shown, it can be seen that the phase is relatively pure.

[0030] The BiFe prepared in this example 0.95 Co 0.05 AFM morphology of O3 film Figure 4 As shown, it can be seen that the film grows smoothly.

[0031] The BiFe prepared in this example 0.95 Co 0.05 The hysteresis loop and butterfly curve of O3 film are shown in the figure Figure 5 As shown, good hysteresis loop and butterfly curve can be seen.

[0032] Example 2

[0033] (1) Chemicals cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, and ferric nitrate nonahydrate were mixed into a solution of BiFe 1-x Co x The chemical molar ratio of the O3 element is calculated and weighed, x = 0.10, and then citric acid is weighed, and the weighed mixture is added to a beaker, and then solvents methanol and ethylene glycol are added in sequence, and the volume ratio of methanol to ethylene glycol is 4:1. A magnetic stirrer is placed in the beaker, and the beaker is placed on a table with a constant temperature and uniform magnetic force for uniform stirring. The magnetic speed is controlled, and a uniform solution is obtained after a period of time. The stirring time is 40 minutes, and the magnetic speed is 300r / min;

[0034] (2) moving the uniform solution of step (1) to a heated magnetic uniform table for stirring and heating for a period of time, the heating temperature is 80°C, the heating time is 1 hour, and the mixed solvent of methanol and ethylene glycol evaporates and generates a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a gel, the oven drying temperature is 140°C, the drying time is 18 hours, scraping the gel from the beaker, putting it into a pre-cleaned mortar and grinding it thoroughly, the grinding time is 0.5 hours, and cobalt-doped bismuth ferrite ceramic powder is obtained, and the cobalt-doped bismuth ferrite ceramic powder is placed in a box furnace for pre-sintering treatment, the heating rate is 4°C / min, the initial sintering temperature is 500°C, the initial sintering time is 4 hours, and the sintering conditions are normal pressure and air atmosphere to obtain a primary calcined powder;

[0035] (3) placing the primary calcined powder in step (2) into a circular mold and subjecting it to pressurization treatment, the pressure of the tablet press is 1 to 2 MPa, the pressurization time is 20 min, and a cobalt-doped bismuth ferrite ceramic block is prepared. The obtained ceramic block is placed in a box-type furnace for calcination, the calcination temperature is 900° C., the heating time is 2 h, and the sintering conditions are normal pressure and air atmosphere, thereby obtaining a cobalt-doped bismuth ferrite ceramic target;

[0036] (4) BiFe 0.90 Co 0.10 O3 target is used for pulsed laser deposition to grow thin films. When the vacuum degree of the chamber reaches 1×10 - 4 When the energy of the pulse laser is adjusted to 250mJ, pre-sputtering is performed. After sputtering, the heating temperature is set to 700℃, the oxygen pressure in the chamber is adjusted to 20Pa, and a bottom electrode is grown first; after the bottom electrode is grown, BiFe 1-x Co x O3 film, set the temperature to 650℃, adjust the oxygen pressure to 13.3Pa; after the growth is completed, introduce 2×10 4 Pa oxygen annealing, cooling rate 10℃ / min, annealing time 45min, BiFe 0.90 Co 0.10 O3 film.

[0037] The BiFe prepared in this example 0.90 Co 0.10 AFM morphology of O3 film Figure 6 As shown, it can be seen that the film grows smoothly.

[0038] The BiFe prepared in this example 0.90 Co 0.10 The hysteresis loop and butterfly curve of O3 film are shown in the figure Figure 7 As shown, good hysteresis loop and butterfly curve can be seen.

[0039] Comparative Example 1

[0040] In this embodiment, x=0.05, and other steps and parameters are the same as those in Embodiment 1.

[0041] The BiFe prepared in this example 0.95 Co 0.05 The XRD pattern of O3 film is as follows Figure 1 As shown, it can be seen that the phase is relatively pure.

[0042] The BiFe prepared in this example 0.95 Co 0.05 AFM morphology of O3 film Figure 4 As shown, it can be seen that the film grows smoothly.

[0043] The BiFe prepared in this example 0.95 Co 0.05 The hysteresis loop and butterfly curve of O3 film are shown in the figure Figure 5 As shown, good hysteresis loop and butterfly curve can be seen.

[0044] Comparative Example 2

[0045] In this embodiment, x=0.10, and other steps and parameters are the same as those in Embodiment 1.

[0046] The BiFe prepared in this example 0.90 Co 0.10 AFM morphology of O3 film Figure 6 As shown, it can be seen that the film grows smoothly.

[0047] The BiFe prepared in this example 0.90 Co 0.10 The hysteresis loop and butterfly curve of O3 film are shown in the figure Figure 7 As shown, good hysteresis loop and butterfly curve can be seen.

Claims

1. A method for preparing a cobalt-doped bismuth ferrite thin film system material, characterized in that: The specific steps include: (1) Chemicals cobalt nitrate hexahydrate, bismuth nitrate pentahydrate, and ferric nitrate nonahydrate were mixed into a solution of BiFe 1-x Co x The chemical molar ratio of the O3 element is calculated and weighed, and then the citric acid is weighed, and the weighed mixture is added to a beaker, and then the solvents methanol and ethylene glycol are added in sequence, and then the beaker is placed on a table with a constant temperature and uniform magnetic force and stirred evenly, and after a period of time, a fully mixed and uniform solution is obtained; (2) stirring and heating the uniform solution of step (1) for a period of time, until the mixed solvent of methanol and ethylene glycol evaporates and generates a large number of bubbles, placing the beaker in a dry constant temperature oven for sufficient foaming for a period of time to obtain a corresponding substance gel, scraping the gel from the beaker, putting it into a mortar and grinding it thoroughly to obtain a cobalt-doped bismuth ferrite ceramic powder, placing the cobalt-doped bismuth ferrite ceramic powder into a box furnace for pre-sintering treatment, controlling the heating rate, initial sintering time, and sintering temperature to obtain a primary calcined powder; (3) placing the primary calcined powder in step (2) into a specially customized mold and subjecting it to pressure treatment to prepare a cobalt-doped bismuth ferrite ceramic block, and placing the obtained ceramic block into a muffle furnace for calcination to obtain a cobalt-doped bismuth ferrite ceramic target; (4) The bulk target was deposited on a LaAlO3 substrate using pulsed laser deposition to obtain BiFe 1-x Co x O3 film.

2. The method for preparing the cobalt-doped bismuth ferrite thin film system material according to claim 1, characterized in that: Step (1) x=0.02-0.10, the molar ratio of citric acid to the metal cation of cobalt-doped bismuth ferrite is 1:1, the volume ratio of methanol to ethylene glycol is 4:1, the stirring time is 40 minutes, and the magnetic speed is 300 r / min.

3. The method for preparing the cobalt-doped bismuth ferrite thin film system material according to claim 1, characterized in that: In the step (2), the heating temperature of the mixed solution is 80-100° C., the heating time is 1 hour, the oven drying temperature is 140° C., the drying time is 18 hours, the grinding time is 0.5 hours, the heating rate is 4° C. / min, the initial sintering temperature is 500° C., the initial sintering time is 4 hours, and the sintering conditions are normal pressure and air atmosphere.

4. The method for preparing the cobalt-doped bismuth ferrite thin film system material according to claim 1, characterized in that: In the step (3), the pressure of the tablet press is 1-2 MPa, the pressing time is 20 min, the calcination temperature is 900° C., the heating time is 2 h, and the sintering conditions are normal pressure and air atmosphere.

5. The method for preparing the cobalt-doped bismuth ferrite thin film system material according to claim 1, characterized in that: The BiFe in step (4) 1-x Co x O3 target is used for pulsed laser deposition to grow thin films. When the vacuum degree of the chamber reaches 1×10 -4 When the energy of the pulse laser is adjusted to 250mJ, pre-sputtering is performed. After sputtering, the heating temperature is set to 700℃, the oxygen pressure in the chamber is adjusted to 20Pa, and a bottom electrode is grown first; after the bottom electrode is grown, BiFe 1-x Co x O3 film, set the temperature to 650℃, adjust the oxygen pressure to 13.3Pa; after the growth is completed, introduce 2×10 4 Pa oxygen annealing, cooling rate 10℃ / min, annealing time 45min, BiFe 1-x Co x O3 film.

Citation Information

Patent Citations

  • Preparation method of cobalt-doped bismuth ferrite system film material

    CN112939484A

  • Preparation method of calcium-doped bismuth ferrite film system material

    CN117144305A